2020
DOI: 10.5194/acp-20-16117-2020
|View full text |Cite
|
Sign up to set email alerts
|

Soil–atmosphere exchange flux of total gaseous mercury (TGM) at subtropical and temperate forest catchments

Abstract: Abstract. Evasion from soil is the largest source of mercury (Hg) to the atmosphere from terrestrial ecosystems. To improve our understanding of controls and in estimates of forest soil–atmosphere fluxes of total gaseous Hg (TGM), measurements were made using dynamic flux chambers (DFCs) over 130 and 96 d for each of five plots at a subtropical forest and a temperate forest, respectively. At the subtropical forest, the highest net soil Hg emissions were observed for an open field (24 ± 33 ng m−2 h−1), followed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 83 publications
(112 reference statements)
0
7
0
1
Order By: Relevance
“…A major objective of our soil pore Hg(0) study was to investigate relationships between Hg(0) in vertical soil pore profiles and evasion of Hg(0) from the soil surface. The variation of soil–air Hg(0) fluxes is shown in Figures S2 and S3 . No relationship was found between soil pore Hg(0) flux and soil pore Hg(0) concentrations at 20 and 50 cm depths.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A major objective of our soil pore Hg(0) study was to investigate relationships between Hg(0) in vertical soil pore profiles and evasion of Hg(0) from the soil surface. The variation of soil–air Hg(0) fluxes is shown in Figures S2 and S3 . No relationship was found between soil pore Hg(0) flux and soil pore Hg(0) concentrations at 20 and 50 cm depths.…”
Section: Resultsmentioning
confidence: 99%
“…In eq , F can be derived from the diffusion of pore Hg(0) or from the photochemical reduction of Hg­(II) on the soil surface during daytime. Combining the simultaneous measurement of soil–air Hg(0) exchange, we estimated the diffusion coefficient between the soil at 3 cm and the atmosphere during daytime ( D s day ) and night-time ( D s night ) and for the entire day ( D s day + night ). In the subtropical forest, the estimated D s day , D s night , and D s day + night were 0.015, 0.013, and 0.014 m 2 h –1 for plot S-A and 0.0098, 0.0096, and 0.0097 m 2 h –1 for plot S-B in the Masson pine forest and 0.010, 0.0076, and 0.0079 m 2 h –1 for plot S-C in the camphor forest, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The regression equations of the Hg 0 flux versus the inverse of the temperature follow the Arrhenius equation (Figure S5). Previous studies also have shown that temperature is one of the main factors determining the atmosphere–soil Hg 0 flux in forest ecosystems. ,, …”
Section: Results and Discussionmentioning
confidence: 95%
“…The atmospheric Hg 0 concentration correlates typically positively with atmosphere−soil Hg 0 exchange at remote sites. 19,71,72 The average atmospheric Hg 0 concentration measured during the atmosphere−soil flux investigations was 0.82 ± 0.16 ng m −3 in Davos-Seehornwald, which was much lower than the background concentrations of Hg 0 in the Northern Hemisphere (1.5−1.7 ng m −3 ). 63 Thus, lower atmospheric Hg 0 concentrations could lead to a higher potential of Hg re-emission from the forest soils in Davos-Seehornwald.…”
Section: Implication For Mercury Cycling In the Forest Ecosystemmentioning
confidence: 96%
“…Additionally, we provide information on standard meteorological parameters (including temperature (T), relative humidity (RH), wind speed (WS), and wind direction (WD)) and trace gases (particulate matter (PM), CO, NO 2 , and SO 2 ), since many factors affecting the variability of GEM emissions include T, atmospheric turbulence, and sunlight, among others (Cizdziel et al, 2019 ; Zhou et al, 2020 ). Meteorological data and trace gas concentrations were downloaded from the Automated Atmospheric Monitoring Network (Red Automática de Monitoreo Atmosférico (RAMA) and Red de Meteorología y Radiación Solar (REDMET)) available at http://www.aire.cdmx.gob.mx/ .…”
Section: Methodsmentioning
confidence: 99%